2014
DOI: 10.1016/j.bbacli.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum fortilin levels is specific for apoptosis and signifies cell death in vivo

Abstract: BackgroundBillions of cells undergo apoptosis each day in the average normal adult. The ability to readily assess the degree of apoptosis in human diseases is hampered by the lack of sensitive and specific serum biomarkers of apoptosis. Fortilin is a novel prosurvival molecule that protects cells against various noxious stimuli. While fortilin is secreted into the extracellular space under certain conditions, the relationship between the serum concentration of fortilin and the presence and extent of apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Another, more recent paper studied serum TCTP (fortilin) levels in mice and humans using a newly developed ELISA. The authors found that TCTP/ fortilin levels are significantly elevated in sera from patients with solid cancers, in response to chemo-or radiation therapy, and concluded that TCTP is suitable as a biomarker for apoptosis in vivo (Sinthujaroen et al 2014). …”
Section: Tctp Dimerisation and Other Extracellular Rolesmentioning
confidence: 99%
“…Another, more recent paper studied serum TCTP (fortilin) levels in mice and humans using a newly developed ELISA. The authors found that TCTP/ fortilin levels are significantly elevated in sera from patients with solid cancers, in response to chemo-or radiation therapy, and concluded that TCTP is suitable as a biomarker for apoptosis in vivo (Sinthujaroen et al 2014). …”
Section: Tctp Dimerisation and Other Extracellular Rolesmentioning
confidence: 99%
“…Cancer cells undergo apoptosis at a higher rate than do normal cells and massively apoptose in response to radiation therapy and chemotherapy. Serum biomarkers of apoptosis could allow clinicians to screen patients for certain cancers and to monitor the response of patients with cancer to anti-cancer chemo- or radiation therapy [4]. …”
Section: Fortilintctp In Human Diseases and Developmental Abnormalmentioning
confidence: 99%
“…To test whether fortilin TCTP exists in the circulating blood, we devised a fortilin TCTP enzyme-linked immunosorbent assay (ELISA) assay system and found that fortilin TCTP circulates in the blood of both mice and humans at the concentration of 47.10 ±11.66 ng/mL and 75.57±45.79 ng/mL, respectively [4]. Fortilin TCTP , an intracellular anti-apoptotic molecule, is also released into the extracellular space via secretory exosomes [3].…”
Section: Fortilintctp In Human Diseases and Developmental Abnormalmentioning
confidence: 99%
See 2 more Smart Citations